Application of distributed generation sources in city power supply - Mirkomil V. Melikuziev (PROBLEMS OF ENERGY AND SOURCES SAVING, 2025)
Relevance: in this article, analyzes the implementation of distributed generation sources in a small city microdistrict characterized by variable and high electric load density. It examines the impact of these sources on the operating modes of low-voltage city power networks and evaluates their effect on the technical and economic performance of city power grids. An essential aspect is the development of a theoretical foundation for designing control systems for distributed generation sources and for planning processes aimed at achieving energy efficiency. The goal: ensuring energy efficiency in low-voltage city power networks is achieved through the application of distributed generation sources and the leveling of electric load profiles by implementing control systems. Methods: methods for calculating the technical and economic performance of city power networks, modeling techniques for distributed generation sources, approaches to achieving energy efficiency, and methods for leveling load profiles of low-voltage urban electricity consumer. Results: the research results are utilized to optimize the loading levels of power grids in the city power supply system through the implementation of distributed generation sources, leveling electric load profiles, and partially reducing energy losses. They are also applied to improve power quality, provide a techno-economic justification and assessment of achieving energy efficiency, and aid in design processes.